2021
DOI: 10.1016/j.artd.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Instability Is the Most Common Indication for Revision Hip Arthroplasty in the United States: National Trends From 2012 to 2018

Abstract: Background As primary total hip arthroplasty volume continues to increase, so will the number of revision total hip arthroplasty (rTHA) procedures. These complex cases represent a significant clinical and financial burden to the health-care system. Methods This was a retrospective review using the National Inpatient Sample. International Classification of Diseases, 9th and 10 th revision codes were used to identify patients who underwent rTHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…Patients with tibia and femur revision procedure codes reported separately were classified as a revision of both components. These patients were then grouped based on the specific indication for rTKA ( Table S1 ) [ 25 ]. The first related diagnostic code listed was used as the primary indication for rTKA.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with tibia and femur revision procedure codes reported separately were classified as a revision of both components. These patients were then grouped based on the specific indication for rTKA ( Table S1 ) [ 25 ]. The first related diagnostic code listed was used as the primary indication for rTKA.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were identified using the International Classification of Diseases, ninth and tenth revision, (ICD-9 and ICD-10) procedure codes ( Table 1 ). For ICD-10 procedure codes, patients required either a revision code or a relevant removal and replacement code as described [ 13 ]. Patients were separated into groups based on whether or not they had a diagnosis of SOT ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In that sample of 292,250 revision THAs, the 3 most common identified indications for revision THA were instability (20.4%), aseptic loosening (17.8%), and infection (11.1%). However, over that study period of 2012 to 2018, the greatest percentage of revision THA diagnosis was in the "other" category at 23.5% [1]. Interestingly, in a prior study of the National Inpatient Sample of 258,461 revision THAs from 2009 to 2013, instability (17.3%), mechanical loosening (16.8%), "other" (16.0%), and infection (12.8%) constituted the top 4 diagnoses [2].…”
mentioning
confidence: 89%
“…As the number of THAs continues to increase, the overall burden of revision THA will subsequently continue to increase. In a recent query of the National Inpatient Sample, Upfill-Brown et al [1] reported that revision THA procedures increased by 28.1% from 2012 to 2018. In that sample of 292,250 revision THAs, the 3 most common identified indications for revision THA were instability (20.4%), aseptic loosening (17.8%), and infection (11.1%).…”
mentioning
confidence: 99%